Effect of Mixed and Intercropping Systems on Dry MaUer and Grain Yields of Component Crops in Arid Environment - Singh, Mahander; Joshi, N L (Annals of Arid Zone, 2016)
A field study on sale, mixed, intercropping and strip cropping of pearl millet [Pcllllisetlim glaucllln (L.) R. Br.] and c1usterbean [Cyamopsis tetragonoloba (L.) Taub.] was conducted to identify the best suitable cropping system for the arid region. Pearl millet and clusterbean grown in alternate row (1:1) gave mean combined dry mailer yields at par with sale cropping of pearl millet but significantly higher than mixed, intercropping and strip cropping. The increase was in the order of 42 to 194%. The 1:1 system also produced maximum grain yield among different intercropping systems. Beller performance of 1:1 system was attributed' to creation of more border rows that resulted in the least influence by shorter component crop through the formation of a two tier system. The highest gross (Rs. 7512 ha-1 ) and net (Rs. 5844 ha-1) returns accrued from alternate row intercropping system (1:1), followed by sale cropping of pearl millet.